Intensive cisplatin/oral etoposide for epithelial ovarian cancer: the Cambridge Gynae-Oncology Centre experience. Issue 3 (March 2016) - Gounaris, Ioannis; Iddawela, Mahesh; Parkinson, Christine; Pratt, Jennie; Hatcher, Helen; Basu, Bristi; Tan, Li Tee; Brenton, James D.; Earl, Helena M.
Abstract : Intensive cisplatin and oral etoposide for relapsed epithelial ovarian cancer (EOC), commonly known as the van der Burg (VDB) protocol, has been reported to improve response rates and progression-free survival. We report on all patients with relapsed EOC treated on the VDB protocol at the Cambridge Gynae-Oncology Centre. From the institutional databases, we identified all patients treated since 2001. We extracted demographic, clinical, treatment, and toxicity data and outcomes. We used Cox regression to identify predictors of survival. A total of 35 patients were treated on the VDB protocol. Toxicity was significant, with grade 3/4 fatigue, nausea and vomiting affecting 46, 46 and 29% of patients, respectively. Six patients had grade 3/4 infection and four (11%) deaths occurred on treatment. Efficacy was encouraging, with a radiological response rate of 43%, a median progression-free survival of 5.8 months and a median overall survival of 14.1 months. No significant difference in efficacy was seen between platinum-resistant and sensitive patients. We report significant activity of the VDB protocol in a routine clinical setting. However, the high rates of serious toxicity and treatment-related deaths among patients treated with palliative intent proved unacceptable. The Cambridge Gynae-Oncology Centre no longer uses this regimen in women with relapsed EOC.